Engineered Biomimetic Nanoparticles-Mediated Targeting Delivery of Allicin Against Myocardial Ischemia-Reperfusion Injury by Inhibiting Ferroptosis - Li M; Wu J; Yang T; Zhao Y; Ren P; Chang L; Shi P; Yang J; Liu Y; Li X; Wang P; Cao Y (International Journal of Nanomedicine)
Minghui Li,1,* Jiabi Wu,1,* Tao Yang,1 Yuhang Zhao,1 Ping Ren,1 Lingling Chang,2 Pilong Shi,1 Jing Yang,1 Yuhang Liu,2 Xiaolei Li,3 Peng Wang,2 Yonggang Cao1 1Department of Pharmaceutics, Harbin Medical University, Heilongjiang, 163319, People’s Republic of China; 2Department of Physiology, Harbin Medical University, Heilongjiang, 163319, People’s Republic of China; 3Department of Pathology, Jiangsu College of Nursing, Jiangsu, 223003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peng Wang, Department of Physiology, Harbin Medical University, Xinyang Road 39, Gaoxin District, Daqing, Heilongjiang, People’s Republic of China, Email wangpeng810122@126.com Yonggang Cao, Department of Pharmaceutics, Harbin Medical University, Xinyang Road 39, Gaoxin District, Daqing, Heilongjiang, People’s Republic of China, Email caoyonggang@hmudq.edu.cnBackground: Cardiac microvascular damage is substantially related with the onset of myocardial ischaemia-reperfusion (IR) injury. Reportedly, allicin (AL) effectively protects the cardiac microvascular system from IR injury. However, the unsatisfactory therapeutic efficacy of current drugs and insufficient drug delivery to the damaged heart are major concerns. Here, inspired by the natural interaction between neutrophils and inflamed cardiac microvascular endothelial cells (CMECs), a neutrophil membrane-camouflaged nanoparticle for non-invasive active-targeting therapy for IR injury by improving drug delivery to the injured heart is constructed.Methods: In this study, we engineered mesoporous silica nanoparticles (MSNs) coated with a neutrophil membrane to act as a drug delivery system, encapsulating AL. The potential of the nanoparticles (named AL@MSNs@NM) for specific targeting of infarcted myocardium was assessed using small animal vivo imaging system. The cardiac function of AL@MSNs@NM after treatment was evaluated by Animal Ultrasound Imaging system, HE staining, and Laser Speckle Imaging System. The therapeutic mechanism was analyzed by ELISA kits, immunofluorescence, and PCR.Results: We discovered that AL@MSNs@NM significantly improves cardiac function index, reduced infarct size and fibrosis, increased vascular perfusion in ischemic areas, and also promoted the function of CMECs, including migration, tube formation, shear stress adaptation, and nitric oxide production. Further research revealed that AL@MSNs@NM have cardio-protective functions in IR rats by inhibiting CMEC ferroptosis and increasing platelet endothelial cell adhesion molecule-1 (PECAM-1) expression.Conclusion: Our results indicated that AL@MSNs@NM significantly reversed CMEC ferroptosis and increased PECAM-1 expression, enhanced cardiac function, and reduced myocardial infarction size. Therefore, this strategy demonstrates that engineered biomimetic nanotechnology effectively delivers AL for targeted therapy of myocardial infarction.Keywords: neutrophil membrane, ischemia-reperfusion, allicin, cardiac microvascular endothelial cells, ferroptosis